Study of Intercellular Adhesion Molecule-1 (ICAM-1) in Bone Homeostasis - Kong, Lingbo; Yang, Xiaobin (Current Drug Targets, 2020)
Although studies have established the role of integrins in bone homeostasis, especially in osteoclastogenesis, and these molecules are novel and promising therapeutic drug targets for bone loss diseases, such as: osteolysis, the cellular mechanism still elusive. Bone homeostasis takes place through the interaction of bone cells (osteoblasts and osteoclast) via the activation of intercellular adhesion molecule-1 (ICAM-1), which is a critical submolecule of integrin. In the present study, we reviewed several novel studies on integrins and their submolecule, ICAM-1, in bone homeostasis. In order to demonstrated that ICAM-1 might exert dual effects on osteoclastogenesis by directly affecting the adhesive ability of mature osteoclasts and indirectly participating in RANKL/RANK induced osteoclastic precursors differentiation. Although these results still need to be verified in the future, the extending study about the role of ICAM-1 in osteoclastogenesis will cerntainly provide a promising therapeutic target for the treatment of bone loss diseases.
Keywords: bone homeostasis